THE INTERVENTION ULTRASOUND AND CLOSED KINEMATIC CHAIN EXERCISE MORE EFFECTIVE THAN THE INTERVENTION ULTRASOUND AND OPEN KINEMATIC CHAIN EXERCISE IN REDUCING PAIN IN PATIENTS WTH SCORES KNEE OSTEOARTHRITIS 8-20 PAIN IN THE BADUNG AREA - Purnama, Ni Made Deni; Andayani, Nopi; Wahyuni, Nila; Sugiritama, I Wayan (Majalah Ilmiah Fisioterapi Indonesia; Vol 5 No 1 (2017): Majalah Ilmiah Fisioterapi IndonesiaDO - 10.24843/MIFI.2017.v05.i01.p02, 2018)
ABSTRACT To reduce pain in patients with osteoarthritis of the knee can be given intervention ultrasound and closed kinematic chain exercises and ultrasound intervention and open kinematicchain exercise . This study is an experimental two group pre and post test design with the 20 samples were divided into 2 groups . Measurement decrease in knee pain was measured using a scale of Western Ontario McMaster Universities Osteoarthritis Index ( WOMAC). The result of paired t -test in group 1 test results obtained p = 0.000 , while in Group 2 showed p = 0.000 . In different test the difference between Group 1 with Group 2 using independent sample t -test was obtained p = 0.000 ( p < 0.05 ) , it can be concluded that the intervention ultrasound and closed kinematic chain exercise is more effective than intervention ultrasound and exercise in the open kinematic chain reducing pain in patients with osteoarthritis knee pain score 8-20 in the Badung area . Keywords : Ultra Sound , Closed Kinematic Chain Exercise , Open Kinematic Chain Exercise , pain